2017
DOI: 10.1111/jgh.13462
|View full text |Cite
|
Sign up to set email alerts
|

“We are what our bacteria eat”: The role of bacteria in personalizing nutrition therapy in gastrointestinal conditions

Abstract: The theme for the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 65 publications
0
8
0
1
Order By: Relevance
“…Intake of galacto-oligosaccharides which include legumes, high FODMAP nuts and some vegetables returned to pre-dietary intervention levels. Fiber is an important substrate for bacteria and their fermentation not only inhibits the growth of pathobionts but also produces short chain fatty acids (SCFA)[49] and is associated with microbial diversity. SCFA are an energy source for the colonocytes and play a regulatory role affecting trans epithelial fluid transport[50], decreased inflammation[51], oxidative stress[52], increases epithelial tight junctions[53] and increases intestinal motility[54] and are therefore central to presumed pathomechanisms leading to IBS.…”
Section: Discussionmentioning
confidence: 99%
“…Intake of galacto-oligosaccharides which include legumes, high FODMAP nuts and some vegetables returned to pre-dietary intervention levels. Fiber is an important substrate for bacteria and their fermentation not only inhibits the growth of pathobionts but also produces short chain fatty acids (SCFA)[49] and is associated with microbial diversity. SCFA are an energy source for the colonocytes and play a regulatory role affecting trans epithelial fluid transport[50], decreased inflammation[51], oxidative stress[52], increases epithelial tight junctions[53] and increases intestinal motility[54] and are therefore central to presumed pathomechanisms leading to IBS.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiome, also referred to as our second genome, integrates external signals to exert nutritional, metabolic, and immunomodulatory functions that are relevant to health and well-being of the host. [45][46][47] There are immense opportunities to use personalized nutritional interventions to prevent and/or treat acute and chronic diseases including gastrointestinal 48 and fatty liver diseases, 49 obesity, 36,50 cardiovascular disease 51 and even neuropsychiatric disorders. 52,53 In addition to modulating microbial composition and/or richness, diet composition can impact the microbial metabolome, 47 which could increase or decrease the risk of disease.…”
Section: Future Opportunities For Nutritional Modulation Of the Gut Mmentioning
confidence: 99%
“…Another example could be to increase the intake of fermentable fiber or prebiotics in patients with Irritable Bowel Disease (IBD) to promote the production of short chain fatty acids, which in turn stimulate intestinal hormone secretion, and modify immune function to reduce inflammation. 47,48,54 Despite some promising clinical data, many limitations and challenges currently limit our ability to integrate patient-specific microbial data into the clinical realm. [45][46][47] These range from our ability to implement low cost, high throughput sequencing methods to enable rapid characterization of the microbiome.…”
Section: Future Opportunities For Nutritional Modulation Of the Gut Mmentioning
confidence: 99%
“…A growing body of evidence has shown that gut microbiota play a causal role in driving the development of obesity, diabetes and NAFLD (31)(32)(33)(34). Diet, as one of the most common environmental factors, shapes the gut microbiome (35).…”
Section: Introductionmentioning
confidence: 99%